Chapter The coastal lakes of Campi Flegrei: between biodiversity and anthropization - Jannuzzi, Ferdinando (Proceedings e report, 2020)
Campi Flegrei (from Greek phlegraios = burning) is a volcanic area north west of Naples, extended from Agnano crater until Cuma. Pozzuoli, Bacoli, Monte di Procida e Quarto, some northern neighboroughs of Naples are included along with Ischia, Procida and Vivara islands. In this area there are three coastal lakes: Fusaro, Miseno, Lucrino. Our study analyses geomorphological, botanical, historicaland anthropic features of their ecosystems.